Case report: Management of pregnancy-associated immune thrombocytopenia in a French bulldog with dystocia - Feldman, Rose; Bracker, Kiko; Whelan, Megan (Frontiers in Veterinary Science, 2024)
Introduction: The objective of this case report is to describe diagnosis and management of life-threatening immune thrombocytopenia (ITP) secondary to pregnancy in a dog with concurrent dystocia. Case summary: A 1-year 11-month old female intact French bulldog was referred for management of severe thrombocytopenia and spontaneous hemorrhage during whelping. The thrombocytopenia was progressive from approximately 32 days of gestation. In the absence of an identifiable cause for the thrombocytopenia, the patient was treated for ITP with immunosuppressive therapies and blood and plasma transfusions. The patient was also supported through dystocia until the platelet count normalized so a Caesarean section and ovariohysterectomy (OVH) could be performed. Discussion: This is the first report documenting ITP in a whelping canine. Pregnancy is a known trigger and can affect the clinical course of autoimmune diseases in women, including ITP. It is suspected that this patient’s pregnancy triggered ITP, paralleling what occurs in women.